2011
DOI: 10.1186/1477-5956-9-41
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of pregnancy-related proteins from pig uterus endometrium during pregnancy

Abstract: Many important molecular events associated with implantation and development occur within the female reproductive tract, especially within the uterus endometrium, during pregnancy periods. The endometrium includes the mucosal lining of the uterus, which provides a suitable site for implantation and development of a fertilized egg and fetus. To date, the molecular cascades in the uterus endometrium during pregnancy periods in pigs have not been elucidated fully. In this study, we compared the functional regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…As would be expected, the overall vaginal proteomic composition dramatically shifted throughout pregnancy. At E7.5, we found an increased abundance of proteins that function as structural constituents of the cytoskeleton involved in the regulation of endometrium development and maintenance of placental implantation during pregnancy (67). Although maternal stress did not broadly disrupt vaginal proteomic composition, the antimicrobial protein lactoferrin was dramatically reduced after stress and remained low throughout pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…As would be expected, the overall vaginal proteomic composition dramatically shifted throughout pregnancy. At E7.5, we found an increased abundance of proteins that function as structural constituents of the cytoskeleton involved in the regulation of endometrium development and maintenance of placental implantation during pregnancy (67). Although maternal stress did not broadly disrupt vaginal proteomic composition, the antimicrobial protein lactoferrin was dramatically reduced after stress and remained low throughout pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…These efforts, along with global gene expression studies, have tremendously advanced our understanding of porcine pregnancy and endometrial biology. In recent years, while many global gene expression studies in the porcine endometrium have been conducted on differential gene expression during pregnancy [11][12][13][14], there are very few reports regarding global changes in porcine endometrial proteome during pregnancy [6,15]. Kayser et al [6] reported changes in uterine fluid proteome during early porcine pregnancy and some proteins reported by them are common to this study.…”
mentioning
confidence: 86%
“…Attached to the cervix, the uterus is layered by an endometrial tissue which is capable of physiological remodeling in response to the oestrous cycle and the presence of the embryo (15). Therefore many studies focused on the activation of the uterus genome during pregnancy (16 -19).…”
mentioning
confidence: 99%